Silent gonadotroph pituitary neuroendocrine tumor in a patient with tuberous sclerosis complex: evaluation of a possible molecular link. (23rd August 2018) - Regazzo, Daniela; Gardiman, Marina Paola; Theodoropoulou, Marily; Scaroni, Carla; Occhi, Gianluca; Ceccato, Filippo
Summary: Tuberous sclerosis complex (TSC) is an autosomal dominant multisystem hereditary cutaneous condition, characterized by multiple hamartomas. In rare cases, pituitary neuroendocrine tumors (PitNETs) have been described in patients with TSC, but the causal relationship between these two diseases is still under debate. TSC is mostly caused by mutations of two tumor suppressor genes, encoding for hamartin (TSC1) and tuberin (TSC2), controlling cell growth and proliferation. Here, we present the case of a 62-year-old Caucasian woman with TSC and a silent gonadotroph PitNET with suprasellar extension, treated with transsphenoidal endoscopic neurosurgery with complete resection. Therapeutic approaches based on mTOR signaling (i.e. everolimus) have been successfully used in patients with TSC and tested in non-functioning PitNET cellular models with promising results. Here, we observed a reduction of cell viability after an in vitro treatment of PitNET's derived primary cells with everolimus. TSC analysis retrieved no disease-associated variants with the exception of the heterozygous intronic variant c.4006-71C>T found in TSC2 : the computational tools predicted a gain of a new splice site with consequent intron retention, not confirmed by an in vitro analysis of patient's lymphocyte-derived RNA. Further analyses are therefore needed to provide insights on the possible mechanisms involving the hamartin-tuberin complex in the pathogenesis of pituitary adenomas. However, our data further support previous observations of an antiproliferative effect of everolimus on PitNET. Learning points: Pituitary neuroendocrine tumors (PitNET) in patients with tuberous sclerosis complex (TSC) are rare: only few cases have been reported in literature. Therapeutic approach related to mTOR signaling, such as everolimus, may be used in some patients with PitNETs as well as those with TSC. We reported a woman with both non-secreting PitNET and TSC; PitNET was surgically removed and classified as a silent gonadotroph tumor. Everolimus treatment in PitNET's-derived primary cells revealed a significant decrease in cell viability. Considering our case and available evidence, it is still unclear whether a PitNET is a part of TSC or just a coincidental tumor.